Differences in the pattern and regulation of mineral deposition in human cell lines of osteogenic and non-osteogenic origin - Rashidi, Hassan; Strohbuecker, Stephanie; Jackson, Leigh; Kalra, Spandan; Blake, Alexander J.; France, Louise; Tufarelli, Cristina; Sottile, Virginie (Karger Publishers, 2011)
Bone marrow-derived mesenchymal stem cells (MSCs) are widely used as a cellular model of bone formation, and can mineralize in vitro in response to osteogenic medium (OM). It is unclear, however, whether this property is specific to cells of mesenchymal origin. We analysed the OM response in 3 non-osteogenic lines, HEK293, HeLa and NTera, compared to MSCs. Whereas HEK293 cells failed to respond to OM conditions, the 2 carcinoma-derived lines NTera and HeLa deposited a calcium phosphate mineral comparable to that present in MSC cultures. However, unlike MSCs, HeLa and NTera cultures did so in the absence of dexamethasone. This discrepancy was confirmed, as bone morphogenetic protein inhibition obliterated the OM response in MSCs but not in HeLa or NTera, indicating that these 2 models can deposit mineral through a mechanism independent of established dexamethasone or bone morphogenetic protein signalling.